2008
DOI: 10.1002/ijc.23202
|View full text |Cite
|
Sign up to set email alerts
|

HPP1‐mediated tumor suppression requires activation of STAT1 pathways

Abstract: HPP1 is a recently discovered gene that is epigenetically silenced in a number of tumor types, suggesting a potential role as a tumor suppressor. However, whether HPP1 has tumor suppressor activity is not clearly known. We have sought to investigate the effects of HPP1 on tumor growth and survival and to identify signaling pathways that mediate HPP1's mechanism of action. Forced expression of HPP1 into HCT116 colon cancer cell lines blocked the ability of HCT116 tumors to grown in vivo in nude mice. In cell cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…In fact, ectopic expression or the addition of purified recombinant TMEFF2 ectodomain promotes neuronal cell survival (9), cell growth (6), and phosphorylation of erbB4 and ERK1/2 (2, 6). However, it has also been suggested that TMEFF2 functions as a tumor suppressor because ectopic expression of full-length TMEFF2 demonstrates in vitro antiproliferative effects (4,10) and suppresses tumor growth in vivo in nude mouse xenografts (10). Consistent with a tumor suppressor activity, Tmeff2 has been shown to be hypermethylated in a number of cancer types (Refs.…”
mentioning
confidence: 89%
“…In fact, ectopic expression or the addition of purified recombinant TMEFF2 ectodomain promotes neuronal cell survival (9), cell growth (6), and phosphorylation of erbB4 and ERK1/2 (2, 6). However, it has also been suggested that TMEFF2 functions as a tumor suppressor because ectopic expression of full-length TMEFF2 demonstrates in vitro antiproliferative effects (4,10) and suppresses tumor growth in vivo in nude mouse xenografts (10). Consistent with a tumor suppressor activity, Tmeff2 has been shown to be hypermethylated in a number of cancer types (Refs.…”
mentioning
confidence: 89%
“…These data consistently indicate that aggressive gastric cancer cells are addicted to lower TMEFF2 expression, which explains the important role that TMEFF2 plays in the progression of gastric cancer. Although TMEFF2 has been reported to mediate tumor suppression in colorectal cancer (29), this study provides the first demonstration of its crucial functions in gastric cancer development by combining high-throughput data analysis and functional assays. The strong correlation between TMEFF2 expression and gastric cancer patient survival, tumor size, and pathologic stage highlights the potential value of TMEFF2 as a novel biomarker for gastric cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer cell lines, overexpression of TMEFF2 leads to upregulation of STAT1 and suppression of growth (Elahi et al 2008). These opposing effects of TMEFF2 acting or not on activation of STAT may reflect the use of distinct signaling cascades by TMEFF2 in different tissues probably modulating different functions, e.g., hormone production versus cell growth.…”
Section: Discussionmentioning
confidence: 99%